MANAJEMEN PADANG PENGGEMBALAAN DI BPTUHPT PADANG MENGATAS - Yoselanda Marta (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2016)
Extensive raising of livestock, especially cattle is still faced with problems of quality and a continuous supply of green feed. Nearly 70% of production costs and maintenance expenditure sourced from cattle feed. Labor efficiency being one of the problems that have not been resolved. Various methods were developed to find a solution that will be able to resolve problems that arise. Breakthroughs were made to bring the solution to be developed. One conducted by BPTUHPT Padang Mengatas is to do with the method of pasture grazing system. With this system is expected able to resolve the issues. This method is considered appropriate to be applied as to minimize feed costs and streamline workforce on the vast farm lands.Keywords : feed, workforce, pasture.